Role playing and academic performance in journalism courses - Vásquez Valencia, Llamil (2020)
The investigation consisted of determining the type of relationship that exists between the didactic method of the role games and the academic performance of the students of the specialty of journalism of the EAP of Social Communication at the UNMSM in the period 2017-II. The type of research is descriptive causal correlational. The design is non-experimental descriptive correlational causal, quantitative and cross-sectional. The conclusion is that there is a direct and significant relationship of r = 0.633 between role plays and students’ academic performance. The findings recommend that more pedagogical training be given to the professors of the Journalism specialty of the EAP of Social Communication at the UNMSM to systematize and evaluate the application of role-playing games in order to favorably affect the academic performance of the students and in their development as future journalism professionals.